KAJIAN KOMPARATIF KONSEP DAN PRAKTIK RAHN EMAS PADA PT. BRI SYARIAH KCP GRESIK - Zaidatin Nazila; Iwan Triyuwono (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study was conducted to determine the suitability of the concept of sharia lien (Rahn) with its implementation at PT BRISyariah Bank KCP Gresik. The study used qualitative methods to approach the type of explanatory case studies. This study describes the implementation of sharia mortgage financing in PT BRI Syariah Bank KCP Gresik and compared with National Sharia Council Law (Fatwa) - Indonesian Ulama Committee (DSN-MUI) and generally accepted accounting standards. Data were obtained through interview, observation, and documentation. Based on this research, concluded that the syariah performance of PT BRIsyariah Bank KCP Gresik has not been maximum yet. There is so much things need to be repaired because of inexpediency of gold rahn practice, especially for determining administration fee, rent fee and multiakad use. Keywords: sharia mortgage (Rahn), administration fee, rent fee, multiakad use.